A structured hazard identification method of human error for shale gas fracturing operation. Issue 5 (4th July 2019) - Hu, Jinqiu; Zhang, Laibin; Wang, Qianlin; Tian, Bin
ABSTRACT: Shale gas fracturing is a complex system of continuous operation. If human errors occur, it will cause a chain reaction, from abnormal events to fracturing accidents, and even lead to abandonment of shale gas wells. The process of shale gas fracturing has many production stages that are complex and the consequence of any error is serious. The human error modes in shale gas fracturing process are mutative. Therefore, human error should be studied in a systematic way, and in a hybrid framework, that is, whole integration of identification, prioritization, reasoning, and control. A new structured identification method of human error in a hybrid framework for shale gas fracturing operation is presented in the article. First, human error is structurally identified based on the human HAZOP method. Second, fuzzy VIKOR method is applied to comprehensive prioritization. Finally, 4M element theory is used to analyze the human error and control its evolution. The method improves the consistency of the identification results through the standard identification step and the identification criterion. Results from a study of feed-flow process indicate that 34 kinds of human errors can be identified, and high-probability errors occur in the behavior of implementation and observation.